INDIVIDUAL MOVEMENTS IN SERVICE FACILITIES BY UTILIZING ONLINE TRANSPORTATION SERVICES IN GEOSPATIAL PRESPECTIVES - Sakinah FS; Anang WN (JSSH (Jurnal Sains Sosial dan Humaniora), 2019)
The application of online transportation services increasingly free any individual to move to have outside activities in more than one place in a certain period of time. Individuals are free to choose what mode of transportation to use and when to use it with transparent costs or even with life insurance provision. This study aimed to find out the individuals' movement in service facilities by utilizing online transportation services in Purwokerto Urban Area in Geospatial Perspective. This study used survey methods and propotional sampling with 40 people as the samples. The results showed that individual movements in various service facilities by utilizing online transportation services were so varied. From a total of 809 movements, 156 movements were done by male user and 653 movements by female users. It is distributed to the destination place from the highest, namely education, economic, community, health and public facilities.